Liability framework for cognitive computing in healthcare: standing at the crossroad / Hartini Saripan ... [et al.] - Saripan, Hartini; Mohd Shith Putera, Nurus Sakinatul Fikriah; Abdullah, Sarah Munirah; Abu Hassan, Rafizah; Abd Ghadas, Zuhairah Ariff (Universiti Teknologi MARA, 2021)
Digitization across the healthcare industry has witnessed the advent of emerging Cognitive Computing (CC) healthcare technologies that improve diagnostic accuracy and efficiency, predict illnesses, automate routine healthcare tasks, and refine processes and care beyond human capabilities. Increased adoption of this technology can be attributed to its ability of processing enormous amounts of data promptly in addressing specific queries and producing customized intelligent recommendations. While CC's trans formative technologies offer profound benefits to the healthcare industry, it also carries an unpredictable burden of risk and mistakes with damaging consequences to patients. At this juncture, CC's legal place in healthcare is largely undefined as the applicable liability framework is ambiguous. CC fits into the traditional liability rules in a piecemeal manner; however a single theory of recovery sufficiently addressing the potential liability questions arising from a computer system capable of practicing medicine and possessing the ability of parsing through enormous data for better patient outcomes is absent. The present research therefore sets out to chart the analysis of cases involving emerging medical technologies comparable to CC, in hope of examining ways in which the traditional theories of liability is projected to develop in adapting to this novel contrivance. A doctrinal and case study methods formed an integrated qualitative approach adopted by this research in opting the deployment of emerging medical technologies akin to CC and the bearing it has on the imposition of liability in the United States. CC's potential contributions to healthcare are revolutionary, however its legal repercussions are just as alarming and therefore demands for more discussion in addressing the concerns.